PENGARUH MODEL PEMBELAJARAN INKUIRI BERBANTUAN POWER POINT TERHADAP HASIL BELAJAR FISIKA PADA MATERI POKOK GERAK HARMONIK SEDERHANA SISWA KELAS X SEMESTER II SMA NEGERI 4 TEBING TINGGI T.P 2016/2017 - IRWAN SUSANTO (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2018)
This study aims to determine whether there is a Significant Effect of the Use of the Power Point Assisted Inquiry Model on Physics Learning Outcomes in Simple Harmonic Motion Subjects of Class X Second Semester Students of SMA 4 Tebing Tinggi T.P. 2016/2017 This research is a quasi-experimental study conducted at SMA Negeri 4 Tebing Tinggi with a population of all class X students totaling 150 people, consisting of 5 (five) classes (IPA1 -IPA5) in parallel, two class research samples taken by cluster random sampling as a class experiment in science class 5 by using the model of Power Point Assisted and -IPA1 class as a control class using the direct learning model, each of which consists of 30 students. The instruments in this study used the Multiple Choice test as many as 18 questions that had been tested to students outside the sample to determine the validity, reliability, power difference and the level of difficulty of the questions. The results showed that the average value of the experimental class pretest was 40.36 and the standard deviation was 11.57. The mean of the control class was 42.03 and the standard deviation was 11.37. From the hypothesis testing using SPSS 22 obtained a sign (2-tailed) = 0.576 and α = 0.05 because the sign> α (0.576> 0.05) this shows that, the initial ability of the two classes is the same. Then given a different treatment then at the end of the lesson given a post-test, the average value of the experimental class was 79.07 and the standard deviation was 8.96 and the average value of the control class was 70.37 and the standard deviation was 9.93. From the SPSS 22 test obtained a sign (2-tailed) = 0.01 and α = 0.05 because of the sign <α (0.01 <0.05) this shows that there is a significant influence on the use of Learning Model Help-Pointed Inquiry on Physics Learning Outcomes in the subject matter of Simple Harmonic Motion in the second semester of class X SMA Negeri 4 High College TP 2016/2017.